Neurofeedback training for young atlete - Kovaleva, A.V.; Kvitchastyy, A. V.; Bochaver, K.; Kasatkin, V. N. (International Journal of Psychophysiology, 2012)
Neuromodulation by means of electroencephalography biofeedback (neurofeedback) is used to promote self-regulation. This general method has been applied in a variety of neurobehavioral problems and disorders. Neurofeedback is also used in peak performance training, to optimize cognitive and affective status in the absence of clinical diagnosis. When quantitative EEG (QEEG) is available as part of client assessment, it is possible to measure neurophysiological activity directly. There are patterns that can be identified that implicate dysfunctional localized regional processing, and these patterns can be used to guide neurofeedback intervention (Johnstone, 2008). Young athletes often have mild to serious problems with their psychological state, especially during championships and games. So, we supposed that neurofeedback training must help them to control their mind and body interactions without any drugs and medications.